2016
DOI: 10.1097/brs.0000000000001604
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Chordoma: Long-term Outcome of a Large Series of Patients Surgically Treated at Two Reference Centers

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 36 publications
1
38
0
5
Order By: Relevance
“…Although, much studies involving sacral chordoma have shown profound results[2932], genomic determinants for skull base chordoma progression remain elusive, urging a need for further examination. Towards this goal, we have characterized genomic and transcriptomic profiles of skull base chordomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although, much studies involving sacral chordoma have shown profound results[2932], genomic determinants for skull base chordoma progression remain elusive, urging a need for further examination. Towards this goal, we have characterized genomic and transcriptomic profiles of skull base chordomas.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, RFS or local control (LC) of skull-base chordomas at 5 and 10 years is 47–76% and 42–71% [3, 4], respectively, while 5- and 10-year estimated RFS for mobile spine chordomas is 58% and 32% [5]. Similarly, the 5-, 10- and 15-year local relapse (LR) incidence is reported to be 30%, 46% and 57%, respectively, in a recently published series of primary and completely resected sacral chordomas [6]. In this study, a plateau in RFS was not observed even at 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…Chordoma is a rare primary bone tumour accounting for 1-4% of all bone malignancies [1][2][3][4][5], arising in the sacrum (50-60%), skull base (35%) or vertebral bodies (15%) [5,6]. En bloc resection has been the mainstay of the treatment [5,[7][8][9][10][11], although recent evidence has underlined the increasing role of adjuvant radiotherapy [12][13][14][15][16]. Although chordoma is histologically characterized as low grade, it is highly recurrent and aggressive and associated with a poor prognosis [17].…”
Section: Introductionmentioning
confidence: 99%